A Case of Early Gastric Cancer with Adachi Type Ⅵ Vascular Anomaly Treated by Laparoscopic Distal Gastrectomy - Kawada, Junji; Mizuno, Manatsu; Fukada, Akio; Nakano, Masaya; Murotani, Masatoshi; Nagano, Shinnosuke; Yoneda, Naoki; Kidogami, Shinya; Mokutani, Yukako; Kishimoto, Tomoya; Hashimoto, Yasuji; Hirose, Hajime; et al. (Gan to kagaku ryoho, 2022)
We report a case of early gastric cancer with Adachi Type Ⅵ vascular anomaly treated by laparoscopic distal gastrectomy. An 81-year-old woman was admitted because of anorexia, and was diagnosed with early gastric cancer. Preoperative MDCT revealed Adachi Type Ⅵ vascular anomaly, where the hepatic artery does not appear at the superior border of the pancreas. The patient was treated successfully with laparoscopic distal gastrectomy with D1+lymph node dissection. At surgery, we identified the portal vein, then, dissection of No. 8a lymph nodes was performed. The postoperative course was uneventful and the patient was discharged 10 days after surgery. The final pathology result showed gastric cancer, M, Less, Type 0-Ⅱc+Ⅲ, 58×50 mm, tub1>pap, pT1a(M), Ly0, V0, pN0(0/40), H0, P0, M0, pStage ⅠA. We understand the arterial running pattern before surgery by using MDCT, and performed laparoscopic surgery safely.